Patterns of care for malignant pleural mesothelioma patients compensated by the Dust Diseases Board in New South Wales, Australia. Issue 4 (1st April 2013) - Kao, S. C.‐H.; Clarke, S.; Vardy, J.; Corte, P.; Clarke, C.; van, N.
Abstract Background The silent epidemic of mesothelioma in Australia is steadily increasing, and 30% of cases occur in New South Wales (NSW). Aim To describe the patterns of care and outcomes of patients with malignant pleural mesothelioma (MPM) in NSW. Methods MPM patients in NSW applying for compensation at the NSW Dust Diseases Board from 2007 to 2009 were included. Survival from time of diagnosis was determined by the Kaplan–Meier method. The Chi‐squared test was used to determine if there was an association between utilisation of treatment and geographical location. Results A total of 138 patients was included: median age was 72.5; 91.3% male; 60.1% epithelial subtype; and 65.2% lived in major cities. All patients had at least one chest X‐ray and computed tomography scan, and 21% had a positron emission tomography scan; 93.5% and 4.3% had histological or cytological confirmation respectively. Thoracoscopy (59.4%) was the most commonly used diagnostic procedure. Treatment utilisation: 53.6% chemotherapy; 35.5% radiotherapy; 9.4% extrapleural pneumonectomy (EPP); and 72.5% had palliative care involvement. There were no major differences in treatment utilisation between patients living in major cities and those in regional NSW (chemotherapy P = 0.42; radiotherapy P = 0.13 and palliative care P = 0.60), except for a higher rate of EPP in regional patients (16.7% vs 5.6%; P = 0.03). Median survival was 9.7 versus 12.3 months for city and regional patients respectively (P = 0.22). Conclusion Survival and treatment utilisation was not significantly different between MPM patients living in major cities and regional NSW, except for a higher rate of EPP in patients in regional NSW.